Genetic variants in fas signaling pathway genes and risk of gastric cancer. Issue 4 (11th September 2013) - Hyland, Paula L.; Lin, Shih‐Wen; Hu, Nan; Zhang, Han; Wang, Lemin; Su, Hua; Wang, Chaoyu; Ding, Ti; Tang, Ze‐Zhong; Fan, Jin‐Hu; Qiao, You‐Lin; Xiong, Xiaoqin; et al.
<x xml:space="preserve">Abstract</x> Populations in north central China are at high risk for gastric cancers (GC), and altered FAS‐mediated cell signaling and/or apoptosis may contribute to this risk. We examined the association of 554 single nucleotide polymorphisms (SNPs) in 53 Fas signaling‐related genes using a pathway‐based approach in 1758 GC cases (1126 gastric cardia adenocarcinomas (GCA) and 632 gastric noncardia adenocarcinomas (GNCA)), and 2111 controls from a genome‐wide association study (GWAS) of GC in ethnic Chinese. SNP associations with risk of overall GC, GCA and GNCA were evaluated using unconditional logistic regressions controlling for age, sex and study. Gene‐ and pathway‐based associations were tested using the adaptive rank‐truncated product (ARTP) method. Statistical significance was evaluated empirically by permutation. Significant pathway‐based associations were observed for Fas signaling with risk of overall GC (p = 5.5E‐04) and GCA (p = 6.3E‐03), but not GNCA (p= 8.1E‐02). Among examined genes in the Fas signaling pathway, MAP2K4, FAF1, MAPK8, CASP10, CASP8, CFLAR, MAP2K1, CAP8AP2, PAK2 and IKBKB were associated with risk of GC (nominal p < 0.05), and FAF1 and MAPK8 were significantly associated with risk of both GCA and GNCA (nominal p< 0.05). Our examination of genetic variation in the Fas signaling pathway is consistent with an association of altered Fas signaling and/or apoptosis with risk of GC. As one of the first attempts to investigate a pathway‐level association, our results suggest that these genes and the Fas signaling pathway warrant further evaluation in relation to GC risk in other populations.